NEW DEVELOPMENTS IN MORPHOLOGICAL DIAGNOSIS OF ISCHEMIC STROKE IN THE VERTEBRO-BASILAR BASIN - Hryhorova, I. A.; Ibragimova, O. L.; Eskin, O. R.; Tykhonova, L. V.; Hryhorov , N. N. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Clinical manifestations of ischemic stroke in the VBB depend on many factors and their diagnosis is often difficult due to atypical clinical presentation and rare classic symptoms [1; 2; 8]. The pathomorphological comparison of changes in the brain in patients who died of ischemic vertebrobasilar and carotid stroke. In VBB stroke stenotic lesion precerebral and intracerebral vertebral artery segments are of most important etiopathogenetic importance. Maximum intensity of the pathological changes in ischemic stroke occurs at 2-3 days of onset of irreversible damage of structural elements of the nervous tissue in the area of the primary ischemic lesion.